eHealth, teledentistry and health workforce challenges: results of a pilot project - Orsolya Németh; Fanni Simon; Abdallah Benhamida; Márton Kivovics; Péter Gaál (BMC, 2022)
Abstract Background In the twenty-first century, health systems have to cope with the challenges posed by their rapidly changing environment. Among these changes, the emergence of digital health solutions is an opportunity to make health systems better, but also a compelling force to change. Community dentistry is one area of health care, where the rapid technological development has the potential for substantial performance improvement benefitting dental patients in terms of access to care and conveniance. Methods This study is based on a survey of the dental care provided by three units (Oral Medicine, Periodontology, Orthodontics) of the Department of Community Dentistry, Semmelweis University, Budapest. During a period of 12 weeks, we have collected time balance data on 1131 patients, 539 in the traditional and 592 in a pilot teledentistry setting, in order to estimate how much time could be spared by monitoring patients through videoconferencing instead of face-to-face visits. Results According to our findings, teledentistry has the potential to shorten the visit with an average of 5-10 min per patient, which adds up to 58-116 work hours in a year. If the pilot was rolled out to all the 13 chairs of the surveyed 3 specialties (orthodontics, periodontology and oral medicine) the time saving would sum up to 186 workdays in one shift alone, which would translate to close to 4500 additional patients per year, considering remote patient monitoring cases alone. Further, if inactive doctors and highly qualified dental hygienists were involved in delivering telecare, 2.67 times as many workdays could be spared, which would allow about 12,000 more patients treated per year. Conclusions The rapid development of digital health technologies coupled with the evolving task distribution between health professionals have a great potential to improve health system performance in pursuit of population health. Unfortunately, the adaptation to these technological changes is uneven, and without a national strategy, the poor will unlikely benefit from these opportunities in public dental care.